ANALISIS SWOT SERTIFIKAT ELEKTRONIK TERHADAP PENYELESAIAN SENGKETA PERTANAHAN DI INDONESIA - Laura Helena Wiryana (Jurnal Hukum Adigama, 2021)
The role of digitization in every aspect of adult life is now increasingly becoming something that cannot be separated from daily activities, including in the land sector. The existence of land disputes, illegal levies and land mafia syndicates that are not easily traceable, have concluded a solution in improving the protection and legal certainty of land rights ownership documents as well as digital transformation that cannot be prevented or avoided. Electronic certificates also have legal force, legal protection, and legal certainty and can be used as authentic evidence in the form of writing if a dispute enters the realm of a civil court. Its effectiveness as protection is also very influential, therefore electronic certificates have the same provisions and equality with conventional certificates. So in this study, the author aims to show how effective electronic certificates are in resolving existing land disputes. The research method used by the author is juridical normative and packaged in the form of swot analysis.